Virtual Summer Undergraduate Mentorship Program for Students Underrepresented in Medicine Yields Significant Increases in Self-Efficacy Measurements During COVID-19 Pandemic: A Mixed Methods Evaluation (Mary Ann Liebert, 2021)
Purpose: The barriers that Black and Hispanic/Latinx students underrepresented in medicine (URiM) face while seeking biomedical careers have been identified, including lack of career preparation and social support. Yet it is unclear how the COVID-19 pandemic has impacted their decisions and progress toward their occupational goals. Methods: Adapting to the precautions necessitated by the COVID-19 pandemic, the authors conducted a mixed-methods evaluation of our 2020 virtual summer URiM biomedical mentoring program, using both quantitative and qualitative pre- and post-program questionnaires to measure the students' perceptions of their preparation and self-efficacy for applying to health professional schools. Results: Themes were extracted from qualitative data through thematic analysis. When students were asked how the COVID-19 pandemic affected them, two themes and subthemes emerged: (1) loss of supportive environment, (1.1) challenging learning environment, (2) derailed or uncertain future, and (2.2) COVID-19 hitting home. When students were surveyed about their online experience at the end of the program, the themes (3) supportive community and (4) inspired and reinforced goals appeared. In addition, quantitative data examined through statistical analysis revealed that the students' career self-efficacy improved significantly after program participation. Conclusion: Our results indicate that the COVID-19 pandemic has further challenged URiM students with pre-existing career obstacles. The outcomes also demonstrate that it is possible to virtually provide URiM students with socioemotional support and increase their career self-efficacy. Overall, frequent evaluations are encouraged to better understand the dynamic challenges of URiM students, improve the design of health career ?pipeline? programs, and diversify the physician workforce to address racial health inequities.